Patient safety culture and associated factors of regional public hospitals in Addis Ababa - Teshome Yayehrad; Yeneneh Getachew; Workineh Muluken (BMC, 2024)
Abstract Background Patient safety culture is the result of individual and group values, attitudes, perceptions, competencies, and patterns of behavior that determine the commitment, style, and proficiency of health providers' safety management. Globally, millions of adverse events occur annually, with a significant burden on low- and middle-income countries. The burden of injuries and other harm to patients from adverse events is likely one of the top 10 causes of death and disability worldwide. This study aimed to assess patient safety culture and its associated factors in regional public hospitals in Addis Ababa. Methods An institution-based cross-sectional study was conducted among 494 healthcare professionals working at regional public hospitals in Addis Ababa. The data were collected using a pretested structured self-administered questionnaire from June 3 to July 30, 2023. The data were entered into Epi info version 7.2 and exported to SPSS version 26.0 for analysis. Binary logistic regression analysis was used to determine the associations between the patient safety culture (dependent variables) and socio-demographic factors, health care providers and system's. Multicollinearity was checked using VIF, and the adequacy of the final model was assessed using the Hosmer and Lemeshow goodness-of-fit test. Result Overall, 48.8% (95% CI: 44.3-53.1) of participants had a good patient safety culture, for a response rate of 93.3%. Factors significantly associated with patient safety culture, as identified through factor analysis, included having 6-10 years of experience (AOR = 1.81, 95% CI = 1.13-2.88), having more than 11 years of experience (AOR = 3.49, 95% CI = 1.27-9.56), reporting adverse events (AOR = 2.47, 95% CI = 1.37-4.45), participating in patient safety programs (AOR = 3.64, 95% CI = 1.91-6.92), and working in obstetrics and pediatric wards (AOR = 0.47, 95% CI = 0.23-0.94) and (AOR = 0.21, 95% CI = 0.097-0.44), respectively. Conclusion The overall level of patient safety culture in regional public hospitals was low (< 75%). Factors such as having 6 or more years of experience, reporting adverse events, participating in patient safety programs, and working in obstetrics and pediatric wards were significantly associated with patient safety culture.